PENGEMBANGAN E-MODUL INTERAKTIF PADA MATA PELAJARAN PENDIDIKAN PANCASILA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VIII DI MTS NEGERI 2 LABUHANBATU UTARA - Amanda Pulungan, Nabila; Dharma, Surya; El Muhtaj, Majda; Habeahan, Sampitmo; Rachman, Fazli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the learning of Pancasila Education which is still dominated by conventional methods and the minimal use of interactive and systematic digital learning media so that students' critical thinking skills have not developed optimally. This study aims to determine the level of validity, practicality, and effectiveness of Canva-based interactive e-modules in the Pancasila Education subject of Digital Literacy in National Diversity. The research method used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were students of class VIII-1 MTs Negeri 2 Labuhanbatu Utara. Data collection techniques included observation, interviews, documentation, validation questionnaires from material experts and media experts, practicality questionnaires from teachers and students, and pretest and posttest tests. The results showed that the interactive e-module obtained a validation percentage of material experts of 91.8% and media experts of 89% with a very valid category. The results of the teacher practicality test obtained a percentage of 94% and students of 96.56% with a very practical category. The effectiveness test results showed an N-Gain value of 0.7029, a high score, indicating that the Canva-based interactive e-module was effective in enhancing students' critical thinking skills. Therefore, the Canva-based interactive e-module is valid, practical, and effective for use in Pancasila Education learning.